Multimedia de apoyo a la formación en valores enmarcados en los principios del buen vivir (Sumak Kawsay) de las áreas básicas, dirigido a estudiantes que cursan el octavo, noveno, y décimo año de educación general básica del colegio nacional mixto “8 de Diciembre” San Pedro de la Bendita del cantón Catamayo periodo lectivo 2012-2013 - Maldonado Calderón, Carlos Stalin (2014)
The present multimedia this directed to the children that are educated in the National School "8 de Diciembre" of the parish San Pedro of the Saint, corresponding to all the areas of Basic General Education. Which makes reference to the practices of the Good one to Live in each curricular block of the different subjects from eighth to tenth year of Basic Education, through the presentation of texts with data informative generals, images and videos about different behavior attitudes and coexistence that we should assume all the Ecuadorians in the daily life. Achieving compactar all the elements in a single interactive multimedia of character educational support, using the program Flash Marinates CS5.Application that served as platform to build the same one. The content that possesses this multimedia this referred and he/she keeps precise relationship with the texts emitted by the Ministry of Education and Culture for each course of Basic General Education, in each curricular block to introduce the students according to the contents treaties to a reflection space and formation in values to put in he/she practices in the daily life. Applying for you interview it, interviews and the respective observation records, directed to the children and girls of Ninth up to Tenth year of Basic General Education; and the educational ones that impart the four subjects. Likewise you uses material bibliographical chord to the study topic and taken data of pages web. The results obtained when putting in execution the multimedia have been favorable, since it has been fulfilled the objectives outlined in a beginning, being experienced a great acceptance on the part of the students and educational who have manifested their pleasure and the possible advantages that will be obtained when using it in their hours class. This way we are contributing with the new curriculum in the basic areas and in the process teaching learning of the students in this facility who you/they have an interactive multimedia of support at your disposal for the educational one, easy to manipulate, amusing and agile in the processes that he/she offers for the four basic subjects, fear relating to you practice them of the Good one to Live off each curricular block.